FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA (PERIODE 2011-2015) - Syaiful Latif, 13.05.52.0013; Aini, Nur (Students' Journal of Accounting and Banking, 2017)
The study examines the effect Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Profit Share Financing and Murabaha Receivable on Return On Asset (ROA). The population in this research is Islamic Commercial Bank listed in Bank Indonesia are supervised OJK in 2011-2015. The sampling method used purposive sampling with the observation period from 2011 to 2015. Relationship and (or) influence between variable is described by using multiple regression analysis. The result of this study indicate that Capital Adequacy Ratio (CAR) and Non Performing Financing (NPF) has negative effect on Return On Asset (ROA). Whereas Financing to Deposit Ratio (FDR) and Murabaha Receivable has positive effect on Return On Asset (ROA) and Profit Share Financing has no effect on Return On Asset (ROA).Keywords: Return On Asset (ROA), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Profit Share Financing, and Murabaha Receivable